Indonesia's Food Security Challenges: How Food SOE Optimizes its Role? - Maun Jamaludin (Research Horizon, 2022)
The problem of food security has always been an important and urgent concern for Indonesia. The greater uncertainty in food production, greater price volatility, increased demand due to population growth and rising incomes, uncertain climate change, and natural disasters are still latent problems. Strategic, sustainable, and comprehensive efforts that can overcome these challenges must be immediately carried out to ensure the availability of sufficient and equitable food availability. This article reviews the role of Bulog as a state-owned enterprise (SOE) established to ensure the availability and security of domestic food. With the presence of Bulog, it is hoped that food availability will be maintained at any time and place at affordable prices, especially for low-income households. Comprehensive food and agriculture policies that can respond to future challenges must be followed up in the form of policy implications in each sector and the implications of various relevant institutions. The food security system must be created based on efficient food self-sufficiency and optimal levels of buffer stocks. For this reason, the government must provide adequate policy support so that food self-sufficiency can be realized and Bulog can function optimally.